The interface between football and ethnic identity discourses in Zimbabwe - Lyton Ncube (Taylor and Francis Group, 2023)
This research is based on Fletcher's [2012. “These Whites Never Come to Our Game, What do They Know about our Soccer? Soccer Fandom, Race and the Rainbow Nation in South Africa.” Doctoral diss., University of Edinburgh. United Kingdom] argument that researching sport is not, and should not be restricted to sport but should be seen as opening up wider avenues of enquiry into everyday life. Theoretically, this study combines a Foucauldian discourse and Neo-Gramscian approach, which views popular culture (including football) as a formative site for the play of power, where identities are negotiated and contested in people's everyday lives. Through ethnographic methods, particularly participant observation in purposively selected football stadia, this study qualitatively explores the contribution of Zimbabwe's most followed teams, Dynamos FC and Highlanders FC, in the performance and expression of social ethnic identities in Zimbabwe. Purposively selected songs and chants by football supporters in stadia were subjected to critical discourse analysis. Findings suggest that Highlanders/Dynamos FC matches are a representation of historical and contemporary ethnic conflicts, particularly between the Ndebele and Shona ethnic groups in Zimbabwe.